2022
DOI: 10.1115/1.4054382
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Schrage Equation for Kinetically Limited Evaporation and Condensation

Abstract: The Schrage equation is commonly used in thermofluid engineering to model high-rate liquid-vapor phase change of pure fluids. Although shortcomings of this simple model were pointed out decades ago and more rigorous models have emerged from the kinetic theory community, Schrage's equation continues to be widely used. In this paper, we quantify the accuracy of the Schrage equation for evaporation and condensation of monatomic and polyatomic fluids at the low to moderately high flux operating conditions relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This model has been experimentally corroborated in binary and ternary gas systems for the diffusion of inert gases under uniform pressure from the Knudsen to molecular diffusion regime and thus is applicable to model our system ( 28 , 45 ). A recent numerical study has found that the dusty-gas model is valid even for very low aspect ratio pores such as those used in this study ( 46 ).…”
Section: Methodsmentioning
confidence: 73%
“…This model has been experimentally corroborated in binary and ternary gas systems for the diffusion of inert gases under uniform pressure from the Knudsen to molecular diffusion regime and thus is applicable to model our system ( 28 , 45 ). A recent numerical study has found that the dusty-gas model is valid even for very low aspect ratio pores such as those used in this study ( 46 ).…”
Section: Methodsmentioning
confidence: 73%
“…Using dedicated pressure measurements and modelling of droplet evaporation including kinetic and diffusive resistances to vapour transport 36 , we quantified the vapour fluxes (j r and j c ), as well as the pressure increase in the vicinity of the freezing droplet, Δp r , using miniaturized pressure sensors (see 'Pressure measurement' in the Supplementary Information and Supplementary Figs. 4 and 5).…”
mentioning
confidence: 99%
“…Kinetic theories predict that the initial evaporation mass flux of oil species i is J i = m i / 2 π R T p s a t , i , where T is the temperature. m i , R , and p sat, i are the molecular mass, gas constant, and saturation pressure of an oil species i , respectively . The vapor pressures of the C10 and C19 mixtures are not readily available.…”
Section: Resultsmentioning
confidence: 99%